Local governance dynamics in the Rana Tharu community of Kanchanpur district - Kalauni, Mukund Ballabh (Nepal Sociological Journal, 2025)
The Rana Tharu community, a significant indigenous group spanning Kanchanpur and Kailali districts in Far Western Nepal, holds historical roots tracing back to Rajasthan, India. Their migration to this region is attributed to the aftermath of Mughal forces defeating the great Hindu hero Maharana Pratap in the pivotal Haldighati battle of 1576 A.D. This paper aims to shed light on the enduring socio-economic and cultural challenges faced by this community and investigate the roles and responsibilities of relevant governing bodies. Employing a qualitative research approach, the study engaged in Focus Group Discussions (FGD) with a primary focus on Bhalmansas, Bharras, Chakars, and socially active members of the Rana Tharu community. Distinguished by their distinctive cultural facets within the broader tapestry of the Terai regions in Nepal and India, the Rana Tharus find themselves engaged in an ongoing quest for self-recognition and preservation of their identity. The current constitution of Nepal seeks to decentralize political, financial, and administrative powers, entrusting them to local governance bodies. In this endeavor, certain local authorities have taken steps to formalize socio-cultural organizations, perceiving them as conduits through which regulations and development can permeate to the grassroots level. Noteworthy examples include the Krishnapur and Laljhadi municipalities in Kanchanpur district, which have conferred specific responsibilities upon Bhalmansas and Padhanas of the Rana Tharu socio- cultural traditional institutions, thereby upholding law and order within their respective villages. Furthermore, these institutions have been granted developmental prerogatives within the Rana Tharu communities. Such initiatives exemplify the principles of sound governance at the local level and warrant commendation as indications of transparency and accountability. To reinforce this positive trend, it is advisable to equip community leaders such as Bharra, Padhana, and Bhalmansas with essential communication tools, enabling them to promptly alert villagers about potential untoward incidents and liaise with local authorities and the government to facilitate relief efforts.